Progress on TiO2-based materials for solar water interfacial evaporation - Srishti,; Khandelwal, Khushi; Kumar, Aditya; Sinhamahapatra, Apurba (Frontiers in Chemical Engineering, 2022)
Solar water interfacial evaporation (SWIE) attracts much attention for harvesting clean water. Over the last few decades, researchers prepared an innovative structure of photo-thermal material for high-performance solar water interfacial evaporation. For higher evaporation performance, TiO2-based material gains attention as a promising photo-thermal material due to light absorption capacity. This report has done comparative studies on the conceptual design of TiO2-based material for SWIE. Its structure design and engineering strategies for improving evaporation rates and higher thermal conversion efficiency have been carefully reviewed. Also, the material’s thermal stability and heat management have been analyzed. This review intends to overview current advances in photo-thermal TiO2 material and motivate research and translation efforts from laboratory to large-scale solar water clean water production. Additional benefits of TiO2 material on solar water interfacial evaporation should be investigated beyond containers to solve interconnected water, environmental, and energy progression.